Medical and surgical complications in pregnancy and obstetric labour complications in the Japan Environment and Children's Study (JECS) cohort: a birth cohort study. (2nd October 2020) - Yang, Limin; Yamamoto-Hanada, Kiwako; Ishitsuka, Kazue; Ayabe, Tadayuki; Mezawa, Hidetoshi; Konishi, Mizuho; Shoda, Tetsuo; Sago, Haruhiko; Saito, Hirohisa; Ohya, Yukihiro; ,
Abstract: This study aimed to describe the distribution of pregnancies with medical and obstetric complications based on the Japan Environment and Children's Study (JECS). We evaluated the distribution of the history of obstetric/gynaecological diseases, the history of obstetric labour complications, pregnancy with medical and surgical complications, and obstetric labour complications in participants in the JECS. Of 100, 818 pregnant women with medical record entries after delivery, 15, 305 (15.2%) had medical and surgical complications in pregnancy and 46, 756 (46.4%) experienced obstetric labour complications. The proportion of pregnancies with heart disease, kidney disease and hepatitis was 0.3%, 0.3% and 0.1%, respectively. Gestational diabetes was diagnosed in 2715 (2.7%) women. The proportion of women with mild and severe gestational hypertension was 2.3% and 1%, respectively. The JECS is the largest birth cohort in Japan. These data will provide useful, basic information for perinatal care in Japan. IMPACT STATEMENT: What is already known on this subject? Epidemiological studies have suggested that pre-existing diseases and complications of pregnancy, such as heart disease in pregnancy, gestational hypertension and gestational diabetes, may have implications for pregnancy outcomes, as well as for children's health and development. What the results of this study add? We evaluated the distribution of the history of obstetric/gynaecological diseases, the history of obstetric labour complications, medical and surgical complications in pregnancy, and obstetric labour complications using data from the Japan Environment and Children's Study (JECS). What the implications are of these findings for clinical practice and/or further research? The JECS is the largest birth cohort in Japan. Our data will provide useful, basic information for perinatal care in Japan.